Influência da técnica de irrigação ultrassônica e soluções irrigadoras, na cimentação adesiva de pinos de fibra de vidro - (:unkn) unknown (Universidade Federal do Amazonas, 2016)
The aim of this study was to evaluate the influence of tree final irrigation systems: PPI (Positive Pressure Irrigation), PUI (Passive Ultrasonic Irrigation) and CUI (Continuous Ultrasonic Irrigation) on the push-out resistence of glass fiber posts, using 5.25% NaOCl (sodium hypochlorite) or 2% CHX (chrorexidine) as irrigation solution. Ninety 17 mm length bovine roots were endodontically treated up to K File #80, to a working length of 16mm, using crown-down technique. During the instrumentation all roots received 1ml of irrigation solution (5.25% NaOCl or 2% CHX) between each instrument using a Navitip® needle. The samples were randomly divided into six groups, according to final irrigation and activation system: PPIN (Control 1): PPI + 5.25% NaOCl; PUIN: PUI + 5.25% NaOCl; CUIN: CUI + 5.25% NaOCl; PPIC (Control 2): PPI + 2% CHX; PUIC: PUI + 2% CHX and CUIC: CUI + 2% CHX. For PPIN/PPIC a Navitip® needle was used to deliver the irrigation solution. For PUIN/PUIC the same Navitip® needle was used and the irrigant solution was activated by a stainless steel file E1 Irrisonic® mounted on a EMS® Ultrassonic unit, for 10-seconds. For CUIN/CUIC the irrigation and activation were performed by continuous agitation and irrigant solution delivery , for 10-seconds, using the same stainless steel file E1 Irrisonic® mounted on EMS® Ultrassonic unit. The final irrigation of all groups was performed using 2ml irrigation solution + 1ml 17% EDTA + 2ml irrigation solution. After canal preparation, the fiber posts Whitepost® DC n.2 were cemented with dual cure resin cement RelyX ARC® and adhesive system Single Bond Universal®. The roots were sectioned into 1mm-thick slices, on cervical, medial and apical thirds. After 7 days, the slices were submitted to push-out test on universal testing machine EMIC (0,5mm/min, 150N). Mean values of bond strength (BS) were compared using two-way ANOVA and Tukey’s test (p≤0.05). BS values (±dp) were: PPIN 4.46 (1.43); PUIN 6.13 (2.35); CUIN 7.41 (1.83); PPIC 3.59 (1.70); PUIC 5.49 (1.41); CUIC 6.0 (1.63). Comparing irrigation solutions, the results were similar with each irrigation systems. CUI showed the best bond strenght values and PPI the worst one, similar to PUI. Analyzing the root thirds, CUIN showed significant diferences at apical third and CUIC showed diferences at middle third. Conclusion: CUI was the best activation system, regardless of the irrigation solution choice, providing better results at fiber post bond strenght, mainly at apical third.
Keywords: Irrigantes do Canal Radicular; Pinos Dentários; Push-out; Push-out resistence; Root Canal Irrigant; CIÊNCIAS DA SAÚDE: ODONTOLOGIA